Analisis Putusan Pengadilan dalam Perkara Tindak Pidana Kekerasan Fisik dalam Rumah Tangga - Aris Budiatno; Diding Rahmat; Yunusrul Zen (Universitas Kuningan, 2018)
This research is influenced by one of the cases of domestic violence that occurs in the Kuningan regency in the decision of the District Court of Kuningan No. 11/Pid.Suisse/2016/PN.Kng. This research aims at : a) to know the settings and affection criminal law against criminal acts of physical violence that is done by the husband toward his wife in the Verdict No. 11/Pid.Suisse/2016/PN.Kng, b) to know how the legal consideration of the judges in the execute the decision in criminal case No. 11/Pid.Suisse/2016/PN.Kng, this research carried out in the District Court of brass. The method used is the nomative juridical approach method to examine the law which the umma as norms or rules that apply in the community and become a reference for the behavior of every man. The primary data obtained through interview and research directly with related parties to obtain information to supplement the data while the Secondary Data, namely the data obtained through the literature study with how to read books of scientific, magazines, the internet newspapers and other reading related to research. Findings from this research among others : (1) Setting affection criminal law against criminal acts based on the instruments of the evidence is contained in the letter of charges formulated by the public prosecutor to perform the tasks the prosecution. The demands of public prosecutor to the Justice that the accused should be required to imprisonment for more than 1 (one) year because the works that are done by the perpetrators of inhumane treatment of women (2) Legal Consideration of the judges in undermining the seriousness of the criminal acts against the accused less appropriate because the overturning of the punishment of the perpetrators are perceived to be very lightweight so that during the do not turn aside from the principles or the principles of pemidanaan so judges can execute judgments imprisonment minimum or maximum of berdasasarkan article that charges relate to the accused.Key Words : the Decision of the Judges, Criminal Acts, Domestic Violence AbstrakPenelitian ini dilatarbelakangi oleh salah satu kasus kekerasan dalam rumah tangga yang terjadi di Kabupaten Kuningan dalam Putusan Pengadilan Negeri Kuningan Nomor 11/Pid.Sus/2016/PN.Kng. Penelitian ini bertujuan : a) untuk mengetahui pengaturan hukum pidana materil terhadap tindak pidana kekerasan fisik yang dilakukan oleh suami terhadap istri dalam Putusan Nomor 11/Pid.Sus/2016/PN.Kng, b) untuk mengetahui bagaimanakah pertimbangan hukum hakim dalam menjatuhkan putusan dalam perkara pidana Nomor 11/Pid.Sus/2016/PN.Kng, Penelitian ini dilaksanakan di Pengadilan Negeri Kuningan. Metode yang digunakan adalah yuridis empiris. Data primer yang diperoleh melalui wawancara dan penelitian secara langsung dengan pihak-pihak terkait untuk memperoleh informasi guna melengkapi data sedangkan Data Sekunder, yaitu data yang diperoleh melalui studi kepustakaan dengan cara membaca buku-buku ilmiah, majalah, internet, surat kabar dan bacaan-bacaan lain yang berhubungan dengan penelitian. Hasil penelitian ini antara lain : (1) Pengaturan hukum pidana materil terhadap tindak pidana didasarkan pada alat-alat bukti yang tertuang dalam surat dakwaan yang dirumuskan oleh jaksa penuntut umum untuk melakukan tugas penuntutan. Tuntutan jaksa penuntut umum kepada Majelis Hakim agar terdakwa seharusnya dituntut hukuman penjara selama lebih dari 1 (satu) tahun karena perbuatan yang dilakukan oleh pelaku tidak manusiawi terhadap perempuan (2) Pertimbangan hukum hakim dalam menjatuhkan berat ringannya pidana terhadap terdakwa kurang sesuai karena penjatuhan hukuman terhadap pelaku dirasa sangatlah ringan sehingga selama tidak menyimpang dari prinsip-prinsip atau asas-asas pemidanaan maka hakim dapat menjatuhkan hukuman pidana penjara minimal ataupun maksimal berdasasarkan pasal yang didakwakan kepada terdakwa.Kata Kunci : Putusan Hakim, Tindak Pidana, KDRT